Aerodynamic Properties and Shelter Effects of a Concrete Plate-Insert Sand Fence Along the Lanzhou-Xinjiang High-Speed Railway in Gobi Regions Under Strong Winds - Wang, Tao; Qu, Jianjun; Niu, Qinghe; An, Zhishan; Gao, Yang; Wang, Hongtao; Niu, Baicheng (Frontiers in Environmental Science, 2022)
The Lanzhou-Xinjiang High-Speed Railway runs through high-wind areas in the Gobi Desert, and disasters arising from the effects of blown sand critically endanger the safety of railway operations. To prevent sand deposition on the rail bed, double rows of sand fences composed of concrete columns and plates are installed on the windward side of the railway line. However, the aerodynamic properties and sheltering effects of these fences remain unclear. In this study, the effects of sand fences on boundary wind patterns and sand transport were investigated in the field and in a wind tunnel. The following results were obtained: (1) The wind velocity was efficiently reduced on the leeward side of the first and second rows of fences by 78% and 87%, respectively. Nevertheless, owing to large openings in the fence, the sand-trapping efficiencies of the first and second rows of fences on the leeward sides were only 72 and 63%, respectively. (2) The effective shelter distance (Ds) of the fence is 10 times the height of the fence; however, the horizontal distance between the two rows of fences is much larger than the Ds of the fence. This allows the wind velocity between the fences to rise above the saltation threshold once again, thereby reducing the overall sheltering effects of the double-row of fences. This study will produce a theoretical reference for improving the design and installation of blown-sand control systems in the strong-wind regions of the Gobi.